Preparation and Characterization of Sulfonated Carbon from Candlenut Shell as Catalyst for Hydrolysis of Cogon Grass Cellulose into Glucose - Taslim; Batubara, Dian Halimah; Maulina, Seri; Iriany; Bani, Okta (Asian Journal of Chemistry, 2020)
Cogon grass (Imperata cylindrica) is convertible into glucose by hydrolysis process, which usually requires a catalyst. A solid acid catalyst of sulfonated carbon was used in this work. This study aimed to observe the viability of candlenut shell as carbonaceous source in solid acid catalyst production and to characterize the sulfonated carbon. The carbonization was performed at 250-550 ºC for 4 h, while sulfonation was carried out at 100-180 ºC for 6 h. Sulfonated carbon was then characterized by H+ activity/acid density test, scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) and Fourier transform infrared (FTIR) spectroscopy. Sulfonated carbon was then tested as a heterogeneous catalyst for hydrolysis reaction. The reaction was performed in a stainless steel batch reactor at 100 ºC for 6 h. Glucose formed by hydrolysis was measured by dinitrosalicylic acid (DNS) method. Results of this study suggested that sulfonated carbon derived from candlenut shell may be used as a catalyst for cogon grass cellulose hydrolysis to produce glucose.